Selective Adsorption of Direct Group Anionic Dyes on Layered Double Hydroxide-Chitosan Composites - Nova Yuliasari; Patimah Mega Syah Bahar Nur Siregar; Alfan Wijaya; Amri Amri; Nur Ahmad; Neza Rahayu Palapa; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
In this research, the potential of M2+/Al intercalated chitosan has been evaluated and good ability to reduce dyes in an aqueous solution. M2+/Al intercalated chitosan was prepared by anion exchange method and coprecipitation in a nitrogen atmosphere. Selectivity adsorption was studied to maintain the ability of M2+/Al intercalated chitosan for particle size of direct dyes (direct green, direct red, and direct yellow). To evaluate the adsorption process, M2+/Al intercalated chitosan was conducted with kinetic, isotherm, and thermodynamic parameters. The kinetic data fitted well by pseudo-second order and isotherm fitted Langmuir isotherm with qmax obtained 294.11 and 322.58 mg/g for Zn/Al-chitosan and Mg/Al-chitosan, respectively. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).